Examining the Impact of Health Belief Model-Based Education on Reproductive Health and Family Planning Attitudes Among Married Women - Tülay Ortabağ; Neşe Ataman Bor (Sağlık Bilimleri Üniversitesi Hemşirelik Dergisi, 2024)
Introduction: Reproductive health services include maternal, child, and newborn health, family planning, fertility issues, and reproductive education, primarily benefiting women.Aim: It was aimed to examine the effects of Health Belief Model based instruction on married women protective attitudes toward reproductive health.Method: The study was designed as a quasi-experimental method with unequal groups for pre-test and posttest comparison. A total of 175 women, 35 in the experimental group, 70 in the control group-1, and 70 in the control group-2, who met the study criteria and were determined by a comprehensive power analysis, were included in the study. The pre-test data were collected using the Personal Information Form, the Married Women’s Reproductive Health Attitudes Determination Scale, and the Family Planning Attitude Scale. Experimental group were given a 3-month group training structured according to the health belief model.Results: Between-group differences were not statistically significant at baseline regarding mean knowledge and the constructs of the scales used (p gt; 0.05). After the training, it was determined that the Reproductive Health Attitudes Determination Scale and Family Planning Attitude Scale sub-dimensions and total scores of compared to the control groups, the experimental group had a significantly higher (p lt; 0.05). Similarly, it was noted that following the training, the experimental group's use of efficient family planning techniques and breast self-examination techniques increased noticeably (p lt; 0.05).Conclusion: According to the results, training was determined to have been given had a positive effect on protective attitudes towards reproductive health.